PENGEMBANGAN OBJEK WISATA PULAU CINTA DAN KEHIDUPAN SOSIAL MASYARAKAT SEKITAR (STUDI KASUS MASYARAKAT DESA TELUK KANIDAI KECAMATAN TAMBANG KABUPATEN KAMPAR) - Satria Wirendra Putra; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The tourist attraction of Teuk Jering Hamlet is a tourist village location which is currently being discussed in cyberspace, especially social media. This village has its own uniqueness which is an attraction for a tourist village of Teluk Jering village itself which has a very interesting view, which is a vast expanse of green grass that can refresh the eyes and also the banks of different rivers. The locations of Jering Bay attractions adjacent to the borders of Pekanbaru City and Kampar Regency make many residents from Pekanbaru and other areas deliberately visit Jering Bay. Local residents and their managers are very enthusiastic about this attraction, seen from the spirit of those who try to advance this Love Island tourist attraction to be known and become a tourist attraction favored by tourists by making a number of programs, facilities and government involvement, because these attractions bring change significant to the social and economic life of the local population, this phenomenon attracts writers to research about; efforts to develop tourism objects and the benefits and disadvantages of rural communities in managing Cinta Island attractions, in this study the researchers interviewed 7 informants who were 2 tourist managers, 2 locals who were also traders in tourist attractions, one ninik mamak dusun III who also participated in trading in tourist attractions and 2 more tourists using qualitative methods and triangulated data collection. The interview conducted was a structured interview where the researcher first prepared the interview guidelines. Keywords: Attractions , Social, economic.